Analisis Kebutuhan Media Pembelajaran Matematika Bangun Ruang Pada Siswa Kelas V Sekolah Dasar - Cantika Dinda Karisma; Yuniawatika; Erif Ahdhianto (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
In learning mathematics, students need help understanding geometric material. Students' success in learning geometric shapes is still low because the teacher uses teaching that is still conventional and has yet to implement innovative learning media. Important media used to support the learning process. This research aimed to analyze the media needs in learning geometric material in VA class at SDN Sambirejo 1, which followed the students' character and was practically used to provide a meaningful learning experience. This study employed qualitative research methods by analyzing descriptive data from interviews and observations with fifth-grade teachers and distributing student needs packages. The research found that there were still few learning media in schools, teachers used blackboards and books, no exciting media, especially for geometric material that could help students understand abstract material, and most students needed media in learning. Mathematics, especially geometric material, is needed to increase enthusiasm and motivation during learning. It can be interpreted that students and teachers need game-based media or games that are practical to support the mathematics learning process, predominantly geometric material.